2010
DOI: 10.1159/000281580
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GRP78 on Endothelial Cell Membranes by an ADAM15-Derived Peptide Induces Angiogenesis

Abstract: Impaired angiogenesis is one of the features of ischemic diseases. We have previously identified, by screening a phage display peptide library, a peptide that induces angiogenesis in endothelial cells under hypoxic conditions by binding the cell’s membrane heat shock protein GRP78. Protein data base search identified 4 amino acids (HWRR) of that synthetic peptide present on the ADAM15 metalloprotease domain, a protein considered to be involved in neovascularization. Three peptides were synthesized according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 51 publications
4
32
0
1
Order By: Relevance
“…Using molecular modeling and docking studies, we found that the GIRLRG peptide bound to the residues in the ATPase domain of GRP78. Different peptides and antibodies binding to the ATPase and substrate binding domains of GRP78 have been reported (5,(29)(30)(31)(32). Some of these have been shown to positively or negatively regulate the growth-promoting effects of GRP78, although their modes of action have not been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Using molecular modeling and docking studies, we found that the GIRLRG peptide bound to the residues in the ATPase domain of GRP78. Different peptides and antibodies binding to the ATPase and substrate binding domains of GRP78 have been reported (5,(29)(30)(31)(32). Some of these have been shown to positively or negatively regulate the growth-promoting effects of GRP78, although their modes of action have not been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Adult (3, 6, 12, or 16 weeks of age) male SHR (74-336 g; n=249) or age-matched normotensive Wistar-Kyoto (WKY) rats (80-345 g; n=211) purchased from the Experimental Animal Center of the National Applied Research Laboratories, Taiwan, were used. SHR received an ER stress protector, 18 salubrinal; a superoxide dismutase (SOD) mimetic, 19 tempol; an autophagy inhibitor, 20,21 3-methyladenine (3-MA); bafilomycin A1 or small interfering RNA against GRP78 (siGRP78) 22 or light chain 3 (LC3; siLC3) 23 to inhibit ER stress-induced autophagy. 24 WKY rats received an ER stress inducer, 25 tunicamycin, or Ang II, alone or with additional treatment of tempol.…”
Section: Methodsmentioning
confidence: 99%
“…In particular we selected Peroxiredoxin-2, because of its presence in all the resulting GO terms, and its cognate molecule Peroxiredoxin-6. The heat shock protein 78 kDa glucose-regulated protein was chosen in virtue of its reported membrane localization and its role in angiogenesis (24). Moreover, this protein is present in almost Fig.…”
Section: Comparative Proteomic Analysis Of Membrane Caveolarraft Micrmentioning
confidence: 99%